2016
DOI: 10.1002/ccd.26475
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary effects of renal denervation with saline irrigated catheter on cardiac systolic function in patients with heart failure: A prospective, randomized, controlled, pilot study

Abstract: Results imply that RDN could be safely applied to treatment of HF and probably improve cardiac systolic function and patients' quality of life. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 29 publications
3
45
1
2
Order By: Relevance
“…A series of studies have been shown to significantly improve HF outcomes in both HF animal models and patients. [10][11][12] Our previous study also showed that RDN can improve heart function, which may be associated with inhibiting cardio-renal fibrogenesis. 13) All these studies have suggested that RDN is feasible, safe, and effective for the treatment of HF.…”
mentioning
confidence: 91%
“…A series of studies have been shown to significantly improve HF outcomes in both HF animal models and patients. [10][11][12] Our previous study also showed that RDN can improve heart function, which may be associated with inhibiting cardio-renal fibrogenesis. 13) All these studies have suggested that RDN is feasible, safe, and effective for the treatment of HF.…”
mentioning
confidence: 91%
“…Stimulation of β-adrenergic receptors induces cardiac myocyte apoptosis and fibrosis in the heart [ 6 ].Prolonged stimulation of the β-adrenergic neurohormonal axis has been shown to contribute to the progression of CHF and mortality in both animal models and humans. Amount of studies, whether clinical studies or animal studies showed that RDN could improve cardiac function in heart failure patients or animals by decreasing sympathetic nerve activity [ 7 11 ]. Our research group also showed that RDN improved cardiac function by decreasing cardiac oxidative stress [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…People who might respond to RDN should be identified first. Further, the possible value of renal denervation extends beyond the hypertension field, for example to benefits in atrial fibrillation [103,104] and in reducing heart failure recurrence [105].…”
Section: Renal Denervation (Rdn)mentioning
confidence: 99%